P397 Influence of underlying conditions on disease presentation and diagnostic strategy during pulmonary mucormycosis: Anational study of 114 cases. (20th September 2022) - Coste, Anne; Conrad, Anne; Porcher, Raphaël; Poirée, Sylvain; Peterlin, Pierre; Defrance, Claire; Letscher-Bru, Valérie; Morio, Florent; Gastinne, Thomas; Bougnoux, Marie-Elisabeth; Suarez, Felipe; Nevez, Gilles; et al.
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM:   Objectives: Pulmonary mucormycosis (PM) is a life-threatening invasive fungal infection mostly affecting immunocompromised patients. We aimed to study the influence of underlying conditions on disease presentation and diagnostic strategy during PM. Methods: All PM cases from six French teaching hospitals between 2008 and 2019 were retrospectively reviewed. Cases were defined according to EORTC/MSG 2019 criteria with the addition of diabetes and traumatism as host factors and positive serum or tissue PCR as mycological evidence. Thoracic CT scans were reviewed centrally. Results: Among 114 cases of PM, 52 (46%) were proven and 62 (54%) were probable, including 12 cases with a positive serum qPCR as the sole mycological criterion. Hematological malignancy was the most common risk factor (49%), followed by allogeneic hematopoietic stem-cell transplantation (21%), and solid organ transplantation (SOT, 17%). Fever was the first symptom for 66% patients and was more frequent in patients with neutropenia than in those without (97% vs 52%, P  <.01). A total of 46 (40%) patients had a disseminated infection, which was more frequently reported in neutropenic patients (50% vs 25%, P  <.01). Main dissemination sites were the liver (48%), spleen (48%), brain (44%), and kidneys (37%). Sinusitis was present in 13% of cases. Chest radiological presentation included consolidation (58%), pleural effusion (52%), reversed halo sign (26%), halo sign (24%), vascular abnormalities (26%), and excavation (23%). The excavation was more frequently reported in SOT patients (64%, P  <.01) compared with other groups. Vascular involvement was associated with reversed halo sign and Rhizomucor infection. Neutropenic patients presented more frequently than non-neutropenic patients with ground-glass opacities (75 vs 49%, P  = .01), halo sign (32% vs 10%, P  = .02), and reversed halo sign (35 vs 10%, P  <.01). A total of 83 (73%) patients had a positive fungal culture from any type of respiratory sample. Serum qPCR was positive for 42/53 patients (79%) and respiratory fluid qPCR for 16/21 (76%) patients. In neutropenic patients, BAL culture was less often positive (30% vs 66%, P  <.01), and serum qPCR was more frequently positive (91% vs 62%, P  = .02). A transthoracic lung biopsy was contributive in 8/11 (73%) patients with negative bronchoalveolar lavage (BAL). Serum qPCR was more frequently positive in patients with the main lesion of >3 cm in diameter (91% vs 62%, P  = .02). Rhizomucor spp. Was identified in 31 patients (32%), Rhizopus spp. In 29 patients (30%), Lichtheimia spp. In 24 patients (25%), Mucor spp. In 10 patients (10%) and Cunninghamella spp. In 4 patients (4%). Neutropenic patients were more frequently infected with Rhizomucor (43% vs 13%, P  <.01) and less frequently with Rhizopus (17% vs 50%, P  <.01). Histopathological specimens were available for 48 patients (42%) and revealed Mucorales hyphae in 85% of cases. Patients with a disseminated infection and neutropenia presented more often with angioinvasion than patients with localized disease (50% vs 9%, P  <.01 and 38% vs 13%, P  = .10). Overall, 90-day mortality was 59%. Conclusion: Underlying conditions significantly influenced clinical and radiological presentation and diagnostic tools' contribution. Neutropenic patients present more frequently with dissemination, fever, reversed halo sign, pathological angioinvasion, the negativity of BAL culture, the positivity of serum qPCR, and Rhizomucor infection.